Analisis Putusan Tindak Pidana Pelaku Aborsi Secara Ilegal : Studi kasus: 136/Pid.Sus/2023/PN Byl - Nency Ayu Lianawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Technological advances in all fields always have an impact on society in a nation. Likewise for the Indonesian people. One of the population problems facing the Indonesian nation today is the social behavior of the younger generation, which today is very free. In fact, they will be the next generation of the nation's ideals. This research method was carried out using a statute approach and a conceptual approach containing descriptions of theories, findings and other research materials obtained from reference materials to serve as a basis for research activities. This approach is also known as the literature approach, the judge's consideration in imposing a crime on abortion committed by the defendant is based on the legal basis used by the judge, namely Article 77 A of the Republic of Indonesia Law No. 35 of 2014 concerning the stipulation of government regulations in lieu of Law No. 1 of 2016 concerning the second amendment to Republic of Indonesia Law no. 23 of 2002 concerning child protection became law in conjunction with Article 55 Paragraph 1 to 1 of the Criminal Code. The Panel of Judges in deciding this case looked at the facts at trial and declared the Defendant legally and convincingly guilty of committing a criminal act